Project-Based Learning as a teaching policy: some questions (Praxis Educativa, 2022)
The work analyzes the use given to Project-Based Learning in the voice of educational policy documents whose recommendations have a strong impact on teaching. Since the early 2000s, PBL has been a teaching strategy explicitly considered in different educational policy recommendations, but it is in the 2015-2019 period that it is considered an efficient strategy to improve school performance. In this work, we intend to make a historical journey that allows us to identify the coordinates that give rise to the PBL, its characteristics and its conditions of use; analyze the treatment of PBL in the framework of educational policy for the period 2015-2019; and present some conclusions and pending questions about the use of PBL in the teaching of secondary schools that serve students from social sectors in vulnerable situation.
Keywords: teaching strategy; Project-Based Learning; teaching policies; secondary schools; students in vulnerable situations